HIV prevalence among people who inject drugs in Greater Kuala Lumpur recruited using respondent-driven sampling - Bazazi, Alexander R. (AIDS Behav, 2015)
The HIV epidemic in Malaysia is concentrated among people who inject drugs (PWID). Accurate estimates of HIV prevalence are critical for developing appropriate treatment and prevention interventions for PWID in Malaysia. In 2010, 461 PWID were recruited using respondent-driven sampling in Greater Kuala Lumpur, Malaysia. Participants completed rapid HIV testing and behavioral assessments. Estimates of HIV prevalence were computed for each of the three recruitment sites and the overall sample. HIV prevalence was 15.8% (95% CI: 12.5-19.2%) overall but varied widely by location: 37.0% (28.6-45.4%) in Kampung Baru, 10.3% (5.0-15.6%) in Kajang, and 6.3% (3.0-9.5%) in Shah Alam. Recruitment extended to locations far from initial interview sites but was concentrated around discrete geographic regions. We document the high prevalence of HIV among PWID in Greater Kuala Lumpur. Sustained support for community surveillance and HIV prevention interventions is needed to stem the HIV epidemic among PWID in Malaysia.